Non-newtonian fluid mechanics and complex flows : Levico Terme, Italy 2016 /: Levico Terme, Italy 2016. (2018) - Farina, Angiolo; Mikelić, A (Andro); Saccomandi, Giuseppe; Sequeira, A (Adélia); Toro, E. F
No abstract available